The development of a radiolabelled macromolecule as a therapeutic agent for the treatment of cancer - Driver, Cathryn Helena Stanford (Division of Medical Biochemistry, 2015)
One of the major focus areas of anticancer therapy is the design of new radiotherapeutic agents that are able to specifically target and destroy cancer cells with minimal side effects and damage to healthy, normal cells. This thesis describes studies towards the synthesis of a macromolecular bioconjugate that was designed to: i) co-ordinate a radioisotope through a tetra-amine macrocycle (cyclam), ii) lead to passive tumour targeting via the EPR effect and a suitably large carrier such as human serum albumin and iii) induce active targeting through a glucose moiety recognised by the over-expressed glucose transporters on the surface of highly metabolically active cancer cells. The various cyclam functionalisation strategies explored were relatively unsuccessful, but eventually a bis-aminal cyclam was successfully converted, through nucleophilic substitution, into a precursor pro-conjugate: a di-functionalised cyclam containing a Î²-glycoside tether and a long chain primary alkylamine. The glycoside tether was synthesised via glycosylation of a glycosyl iodide with decandiol followed by oxidation of the terminal hydroxyl group to an acid chloride for cyclam acylation. The second linker attached to cyclam was synthesised by conversion of decanediol to a brominated alkyl amine. This amine would then be converted into a maleimide functionality suitable for Michael addition with a free thiol group contained within the proposed bio-carrier to form the desired bioconjugate. Further studies described towards the synthetic construction of the bioconjugate include: 1) The construction of a maleimide group 2) The attachment of an imaging radioisotope, â ¹â ¹m Tc, or therapeutic isotope, Â¹â °Â³ Pd, to the pro- conjugate and other glucose-cyclam precursors 3) The determination of the potential uptake of the bioconjugate through glucose transporters by using a fluorescent dansyl-glucose compound as a model and monitoring its uptake into WHCO1 oesophageal cancer cells. 4) The HPLC analysis of the coupling of a glucose-maleimide model compound to bovine serum albumin to investigate the Michael addition of the free thiol in HSA to a maleimide 5) The development of a potentially alternative nanoparticle carrier by synthesis of palladium and magnetic nanoparticles with commercially available thioglucose or glucuronic acid moieties as the surface targeting and stabilising agent. In summary, this thesis outlines a number of synthetic, radiological and biological aspects towards the development of a fully functioning radiolabelled macromolecular bioconjugate that could be tested for improved targeted cancer radiotherapy.